2013
DOI: 10.4236/jct.2013.46120
|View full text |Cite
|
Sign up to set email alerts
|

Emotions of Gynecologic Cancer Patients Dealing with Permanent Colostomy: A Qualitative Interview Study

Abstract: Purpose: This study was conducted to describe emotional state of colostomized patients with gynecologic cancer. Patients and Methods: The study employed a qualitative design from May to October of 2010, in a private university hospitals outpatient gnecologic oncology clinic in Ankara, Turkey. Content analysis with an inductive approach had been used to analyze 32 interviews that served as the data base for this study. Interview form that focused on what gynecologic cancer women felt to living with a colostomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Heavily impounded by various societal, cultural and social factors and suppressed by predominant religious beliefs, sexuality continues to be a matter that is challenging to discuss openly and is currently treated as a taboo [22]. According to the SHST, sexuality is still a learning topic, information regarding sexuality is acquired from media, through the use of computers and the Internet and from friends, in this country [19].…”
Section: Discussionmentioning
confidence: 99%
“…Heavily impounded by various societal, cultural and social factors and suppressed by predominant religious beliefs, sexuality continues to be a matter that is challenging to discuss openly and is currently treated as a taboo [22]. According to the SHST, sexuality is still a learning topic, information regarding sexuality is acquired from media, through the use of computers and the Internet and from friends, in this country [19].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested to keep the nurses knowledge and skills up dated to help the colostomy patients (Ardigo & Amante, 2013;Bulkley et al, 2013;Dabirian, et al, 2011;Gül, et al, 2013;Sun et al, 2014). Nurses should be equipped with necessary knowledge and skills to help the colostomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted on 32 gynecologic cancer patients with colostomy in Turkey indicated that patients felt the high need for psychological support from nurses to minimize the fear, worry and anxiety and women going under colostomy were concerned about their body image, self-esteem, social activity and sexuality while in need for support from nurses (Gül, Ayhan, & Tevfik, 2013). Literature further states that colostomy patients go-through lot of stress and feeling undignified.…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature supports the importance of addressing nurses in-service educational needs related to colostomy care. A qualitative study conducted on 32 gynecologic cancer patients with colostomy in Turkey indicated that patients felt the high need for psychological support from nurses to minimize the fear, worry and anxiety and women going under colostomy were concerned about their body image, self-esteem, social activity and sexuality while in need for support from nurses (Gül, Ayhan, & Tevfik, 2013). Literature further states that colostomy patients go-through lot of stress and feeling undignified.…”
Section: Introductionmentioning
confidence: 99%